Water quality and sediment contamination assessment of Pazarsuyu Stream, Turkey using multivariate statistical methods and pollution indicators - Ustaoğlu, Fikret; Tepe, Yalçin (International Soil and Water Conservation Research, 2019)
The spatio-temporal variations of surface water quality and the level of metal contamination in the sediment of Pazarsuyu Stream were determined by using multivariate statistical techniques and pollution indicators, respectively. The water and sediment samples were collected monthly from four different stations along the Pazarsuyu Stream between June 2014 and May 2015 and analyzed using standard methods. Results were assessed according to national and international water quality criteria and the water quality parameters in some stations were found to be over these criteria levels. The present study showed that statistical techniques such as Pearson Correlation Index (PCI), Principal Component Analysis (PCA), Cluster Analysis (CA), One Way ANOVA need to be used to get better information for the studies on the water quality of surface waters. PCA identified six factors accounting for 82.88% of the total variation in the data. The abundance of sediment heavy metals was in the order of Fe > Mn > Zn > Pb > Cu > Cr > Co > Cd. The heavy metal contamination in the sediments was evaluated by applying the enrichment factor (EF), contamination factor (CF), geoaccumulation index (Igeo) and potential ecological risk index (PERI). Pb was heavily contaminated and has a significant enrichment of contamination according to calculated EF values. Therefore, the stream water can be used for irrigation with precaution but extensive treatment required before using for domestic purposes to prevent adverse public health effects.